Designing Research Result-Based Arabic Pragmatic Learning Module On Politeness Principles And Strategies - Arifianto, Muhammad Lukman; Kholisin, Kholisin; Ridwan, Nur Anisah; Izzudin, Iqbal Fathi; Mujahidah, Zulfa Azalia; Muhtar, Siti Nuraeni (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2022)
In the last decade, many studies on politeness in Arabic have been published on various platforms, but until now the results have not been systematically compiled and used as a module or teaching material. In addition, Arabic pragmatics teaching materials, especially regarding politeness principles and strategies, currently do not refer much to the results of the latest research, even though the results of these studies can be used as a basis in the context of applying, testing, or even developing a theoretical framework on Arabic politeness. Therefore, this study aims to design Arabic pragmatics learning modules, especially concerning politeness in Arabic by utilizing the results of these studies. It is assumed that the development of research-based learning modules can enrich learning materials with the latest findings. By utilizing content and thematic analysis, the research results are analyzed systematically and then designed as a learning module based on the lesson plan that has been set. The result shows a bunch of research about politeness in Arabic published in scientific journals and digital repositories. Almost all research refers to the remarkable theoretical framework of politeness principles proposed by Leech (1983), as well as politeness strategies proposed by Brown & Levinson (1987). Although both are relatively old-school frameworks, they still seem relevant to been implemented by some researchers to date. Furthermore, a systematic study of the results of these studies was then composed and designed into an Arabic pragmatic learning module, especially on the topic of linguistic politeness principles and strategies.